ON GENETIC CLASSIFICATION OF CHROMIAN SPINELS IN DEEP-SEATED ROCKS FROM CONTINENTAL STRUCTURES - Genshaft Yu.S.; Ilupin I.P. (My University, 2002)
A large data base of 1821 chromian spinel compositions (Cr2O3 > 2 wt%) in ultramafic nodules from basalts, kimberlites, lamproites, ultramafic massifs, and from the diamond assemblage has been analyzed using mathematical statistics methods. For each spinel component under study (TiO2, Al2O3, Cr2O3, FeO, MnO, MgO), a considerable overlap is observed, spinels with the highest Cr-number (#Cr) being found in the diamond assemblage and those with the highest Mg-number (#Mg), in nodules from basalts. The lowest oxidation degree is detected in spinels from nodules in basalts and from the diamond assemblage. Spinels from ultramafic massifs have the highest oxidation degrees and Fe-numbers. In ultramafic massifs from kimberlite to lamproite through to the diamond type, spinel compositions follow the same variation trends. Spinels from the basaltic group fall away from these trends. Compositional variability of spinels is due chiefly to isomorphic replacement of Fe+2 for Mg and of Al and Mg for Cr. Kimberlite-type spinels have high and broadly variable Ti contents. Igneous and metamorphic/metasomatic origins for spinels of the five groups under study are discussed. Spinel compositions from ultramafic rocks found in continental structures are shown to indicate that at depth beneath these structures, there exist physicochemical conditions for crystallization inherent to all the principal tectonic features of the earth-continents, oceans, and transition zones (island arcs). for Mg and of Al and Mg for Cr. Kimberlite-type spinels have high and broadly variable Ti contents. Igneous and metamorphic/metasomatic origins for spinels of the five groups under study are discussed. Spinel compositions from ultramafic rocks found in continental structures are shown to indicate that at depth beneath these structures, there exist physicochemical conditions for crystallization inherent to all the principal tectonic features of the earth-continents, oceans, and transition zones (island arcs).
Keywords: CLASSIFICATION OF CHROMIAN SPINELS; DEEP-SEATED ROCKS; CONTINENTAL STRUCTURES; KIMBERLITES